Nilai- Nilai Pendidikan Profetik dalam Rutinan Pembacaan Maulid Simtudduror Majelis Muhibbin Rasulullah Yogyakarta - Jarkasih Jarkasih; Wiga Ananda; Tri Indah Annisa; Nur Azizah; Muhammad Ilham Thayyibi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Education can not only be done through formal education. However, education can also be done through community culture. The purpose of this research is to explain the values of prophetic education in the celebration of Maulid Simtudduror at the Muhibbin Rasulullah Yogyakarta assembly. The research method used in this study is qualitative research with a case study approach. Sumbner data there are two primary data sources, namely Habib Usman and Kyai Kuswaedi Syafi'i as well as Islamic books as Science, Epstemology, Methodology and Ethics and Prophetic Ethics Proclamation, both of which are written by Kuntowijoyo, then secondary data sources are documentation related to these activities, namely in the form of junral, papers, theses, and theses related to prophetic education. Data were obtained by participatory observation, interviews and documentation. The results of this research are the value of prophetic education in the reading of Maulid Simtudduror at the Muhibbin Rasulullah Yogyakarta assembly, namely humanist values including tolerance, generosity, social care, and patience. Then the value of liberation includes hard work, firmness and fairness. And the values of transcendence include religious, honesty and discipline.